1999
DOI: 10.1038/sj.bjp.0702384
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of ICS 205,930, a novel type of potentiator of responses to glycine in rat spinal neurones

Abstract: 1 The e ect of a novel potentiator of glycine responses, ICS 205,930, was studied by whole-cell recordings from spinal neurones, and compared with that of other known potentiators, in an attempt to di erentiate their sites of action. 2 The ability of ICS 205,930 (0.2 mM) to potentiate glycine responses persisted in the presence of concentrations of Zn 2+ (5 ± 10 mM) that were saturating for the potentiating e ect of this ion. 3 Preincubation with 10 mM Zn 2+ before application of glycine plus Zn 2+ had an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…[44][45][46] Consistent with this hypothesis, propofol enhances submaximal (EC2-EC20) glycine-evoked responses recorded from recombinant receptors expressed in oocytes 46,47 and glycine-evoked currents recorded from cultured spinal neurons. 7,36 In contrast, Hara et al 8,9 observed neither direct activation nor modulation of glycine receptor currents recorded from acutely dissociated rat hippocampal neurons with propofol (1 and 5 mol/L). Our own data show that while glycine-evoked responses in the optic nerve were potentiated by propofol (which was modest when compared with GABA response modulation) we observed no effect on the strychninesensitive glycine current responses recorded from rat cultured embryonic hippocampal neurons, even at a concentration maximally effective for potentiation of the GABAA current and twice that investigated by Hara et al 9 Higher (supra-anaesthetic) concentrations of propofol may modulate glycine receptors in hippocampal neurons but because they also directly activated the GABAA receptor 10 and resulted in desensitization of the GABA response, we did not examine these concentrations further.…”
Section: Discussionmentioning
confidence: 94%
“…[44][45][46] Consistent with this hypothesis, propofol enhances submaximal (EC2-EC20) glycine-evoked responses recorded from recombinant receptors expressed in oocytes 46,47 and glycine-evoked currents recorded from cultured spinal neurons. 7,36 In contrast, Hara et al 8,9 observed neither direct activation nor modulation of glycine receptor currents recorded from acutely dissociated rat hippocampal neurons with propofol (1 and 5 mol/L). Our own data show that while glycine-evoked responses in the optic nerve were potentiated by propofol (which was modest when compared with GABA response modulation) we observed no effect on the strychninesensitive glycine current responses recorded from rat cultured embryonic hippocampal neurons, even at a concentration maximally effective for potentiation of the GABAA current and twice that investigated by Hara et al 9 Higher (supra-anaesthetic) concentrations of propofol may modulate glycine receptors in hippocampal neurons but because they also directly activated the GABAA receptor 10 and resulted in desensitization of the GABA response, we did not examine these concentrations further.…”
Section: Discussionmentioning
confidence: 94%
“…Structure-activity analyses of tropisetron analogues have provided some insight into the tropisetron structural moieties required for potentiation and inhibition [134][135][136][137][138][139][140][141]. One such analysis concluded that an aromatic ring, a carbonyl group and a tropane nitrogen are required for glycinergic potentiation [134].…”
Section: Tropisetron and Analoguesmentioning
confidence: 99%
“…Glycine receptors also contain modulatory sites. For example, glycine responses can be potentiated by alcohols, different types of anaesthetics (Belelli et al ., 1999; Krasowski & Harrison, 1999), inhaled drugs of abuse (Beckstead et al ., 2000), Zn 2+ (Bloomenthal et al ., 1994; Laube et al ., 1995; Lynch et al ., 1998; Suwa et al ., 2001), some 5‐HT 3 antagonists (Chesnoy‐Marchais, 1996; Chesnoy‐Marchais, 1999; Chesnoy‐Marchais et al ., 2000; Supplisson & Chesnoy‐Marchais, 2000) and some dihydropyridines (DHPs; Chesnoy‐Marchais & Cathala, 2001). Some of these potentiators interact with transmembrane segments (Belelli et al ., 1999; Krasowski & Harrison, 1999; Beckstead et al ., 2000; Mascia et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%